YOUNG PEOPLE ARE OUR GREAT FUTURE - Kayilova Mekhriniso Djuraevna (Bright Mind Publishing, 2025)
In this article, in the last years of independence, the youth policy is reflected in the reforms implemented in the youth activities, in the adopted political decisions. The importance of educating school-aged students in the spirit of patriotism, specific general laws of social society, normative procedures related to youth activities are revealed.
Keywords: Politics, Assembly, Demographic Dividend, Parliament, Concept.